Occurrence and ecological risks of brominated flame retardants and dechlorane plus in sediments from the Pearl River Estuary and Daya Bay, South China. (December 2022) - Hu, Yongxia; Li, Zongrui; Xiong, Jingjing; Zhang, Zaiwang; Yuan, Jiaxin; Tang, Yi; Jin, Tao; Li, Huawei; Wu, Shengjun
Abstract: Considering the phasing-out of polybrominated diphenyl ethers (PBDEs), environmental concerns of PBDE alternatives and dechlorane plus (DP) are rising. Accordingly, this study investigates occurrence and ecological risks of PBDEs, PBDE alternatives and DPs in sediments of two littoral regions, the Pearl River Estuary (PRE) and Daya Bay (DYB), in southern China. Total PBDEs concentrations in surface sediments of the PRE and DYB were in the range (mean) of 0.30–28.7 (8.71) and 0.29–43.4 (6.05) ng/g dw, respectively. DP levels in surface sediments of the PRE (0.004–0.27 ng/g dw) were significantly higher than those in the DYB (0.005–0.24 ng/g dw) ( p < 0.05). BDE 209 was the predominant component, followed by DBDPE, exhibiting regional variations in BFRs usage. Vertical profiles of BFRs and DP in the PRE and DYB sediment cores exhibited clear anthropogenic influences. Risk quotients suggest critical ecological risks of tetra-, penta- and deca-BDE congeners in all the surface sediments. Graphical abstract: Unlabelled Image Highlights: BFRs and DP were determined in sediments from the PRE and DYB of South China. Profiles of PBDE congener compositions exhibited regional differences. Vertical profiles of BFRs and DP in sediment cores showed anthropogenic influences. Risk quotients of exposure to BFRs and DP in sediment were acceptable.